Storying the FEW Nexus: A Framework for Cultivating Place-Based Integrated STEM Education in Rural Schools - Hannah H. Scherer; Amy Price Azano (Education Sciences)
When education in STEM, social science, and the humanities are disconnected from each other and from place, it is inauthentic and nonresponsive to the lived experiences of people and communities. In rural spaces, the Food–Energy–Water (FEW) Nexus, a framework for problem solving and decision-making around these central resources, is salient because of the concentration of FEW resource production and extraction present. Storying the FEW Nexus is an interdisciplinary pedagogical framework that is theoretically rooted in a critical pedagogy of place and socio-ecological systems. Storying the FEW Nexus brings together these two related but distinct frameworks, calling attention to the need for relevant, place-based, and rural-focused narratives within STEM instruction. Developed for K-12 learners in rural places, Storying the FEW Nexus positions STEM knowledge and skills as resources that, alongside local narratives, are vital to the sustainability and viability of communities with unique and intertwined environmental justice histories and current realities. The FEW Nexus is leveraged to support rural learners in developing sustainable solutions to local socio-ecological systems issues. In this conceptual paper, we review the literature base supporting this integrated approach, describe the framework within the context of these aims, and make suggestions for researchers and practitioners.